On-line rotational rheometry for extrusion and compounding operations - Covas, J. A. (2008)
The challenges polymer processing and compounding face nowadays are related not only with the design and control of more efficient equipment but also with the intelligent manipulation of the molecular structure of the materials with a view to obtaining better performing products. Of obvious importance in both cases is the possibility of performing in-/on-line measurements of relevant material properties during processing. Current online rheological measurements are mostly performed at the end of the extruder, after diverting a small amount of melt from the main stream. Although useful from a quality control point-of-view, process optimisation would require the availability of data upstream, where a plethora of physico-chemical phenomena (chemical reactions, physical blending, degradation, etc.) determine the final characteristics of the materials. In this paper, a new on-line rotational rheometer that allows the rheological properties of materials to be monitored as they are being processed in an extruder is presented. The instrument enables such important phenomena as morphology development or reaction kinetics to be followed from changes in the rheological responses measured along the screw axis.